Dampak Kualitas Informasi dan Sistem Aplikasi Shopee Partner terhadap Kinerja Kurir di Kota Medan - Indah Dwi Pancari; Muhammad Irwan Padli Nasution (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2026)
The development of information technology has significantly improved the efficiency of application-based delivery services, including Shopee Partner Driver couriers. However, several issues such as delays in information updates, system errors, and inaccurate delivery data still affect courier performance. This study aims to analyze the effect of Information Quality and System Quality on the Performance of Shopee Partner Driver Couriers in Medan City. This research used a quantitative method with a questionnaire survey distributed to 100 active couriers. The instrument applied a fivepoint Likert scale, and data were analyzed using validity and reliability tests, descriptive statistics, and multiple linear regression analysis with SPSS software. The results indicate that both Information Quality and System Quality have a positive and significant effect on Courier Performance. The coefficient of determination (R²) of 0.625 shows that these two variables explain 62.5% of courier performance variance, while the remaining 37.5% is influenced by other factors. These findings support the DeLone and McLean (2003) model of information system success, emphasizing the importance of system and information quality in enhancing user performance.